STUDENT-MADE VIDEO PROJECT TO ENHANCE STUDENTS’ LEARNING EXPERIENCE - Adelia Puspa (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Student-made video project was implemented in this research to develop students’ English skills in a more meaningful task, and to train the technical and soft skills required for living in 21st century citizenship. The objectives of this research was to find out the most developed English skill in each phase of video project implementation, as well as to analyze whether the students perceive student-made video project as positive learning experiences to develop their 21st century skills in relevant to their future career. Close-ended questionnaire was distributed to 31 students of Management class to obtain quantitative data, while the qualitative data were gathered from group observation, group reports, and semi-structured interviews. The results revealed that in the preparatory phase the students stated that they develop their writing the most, in the production phase speaking skill was trained the most, and in the video presentation phase the students’ reading and listening were the two English skills that developed the most. Moreover, the students also viewed the project as positive learning experience in developing 21st century skills. The skills included self-directed, knowledge creation, collaboration, and digital literacy.However, the roles of teacher in the project work should be taken into a deeper understanding in the future research.